Analisis Penerapan Sistem Pengendalian Personel Pada PT ABC Surabaya - Michael Revelin Ervan Septian; Paramita Nidan Paramesti; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to determine the implementation of the personnel control system at PT ABC Surabaya. The research method used is a descriptive qualitative method while data collection methods are carried out through interviews, documentation and observation. The research results show that the implementation of the personnel control system at PT ABC Surabaya has been implemented effectively except for the placement element.